Advances in Pacific Basin business economics and finance. - Lee, Cheng F.; Yu, Min-teh (Advances in Pacific Basin business, economics, and finance, 2017)
The 2017 APBBEF volume includes studies on financial regulations on financial institutions, research on financial markets, and issues on employment and income inequality. Regulations on insurance contracts and derivatives, bank capital standards and subordinated debt prices, and bank's credit allocation during the financial crises are of great concern to policy makers. On the financial markets, this volume covers stock market activities and their relationship with industrial production growth and housing prices, a further equity premium puzzle, and accounting fraud and audit fees in China. This volume also includes the employment assimilation of marriage and human capital investment inequality and the rural-urban income gap in the Asia-Pacific region. Contributors to this volume include Edward J. Kane (Boston College), J. Huston McCulloch (Ohio State University), Cheng-Few Lee (Rutgers University), Thomas C. Chiang (Drexel University), Chiung-Min Tsai (Central Bank of the Republic of China), Wei-Chiao Huang (Western Michigan University), Hwei-Lin Chuang (National Tsing Hua University), Jingjing Yang (Guangdong University of Foreign Studies), Sayyed Mahdi Ziaei (Xiamen University Malaysia), Ghulam Ali Bhatti (University of Gujrat), and Min-Teh Yu (China University of Technology).